PENGEMBANGAN PERANGKAT PEMBELAJARAN UNTUK MENGUKUR COMPUTIONAL THINKING PADA MATERI PECAHAN DI KELAS IV SD NEGERI 060911 - Siti Sarah Sinaga; Abdul Mujib (STKIP Subang, 2025)
Computational thinking is a way of understanding and solving complex problems using computer science techniques and concepts such as demonstration, pattern recognition, abstraction and algorithms and is seen by many experts as one of the abilities that supports many dimensions of education. This research aims to produce valid and practical learning tools and to measure Computational Thinking in fractional material in class IV of SD Negeri 060911. To evaluate students' computational thinking abilities in fractional material in class IV of SD Negeri 060911. In this research qualitative research methods will be used. with the type of Research and Development (R&D) research. Data collection methods include observation, interviews. The validity of learning tools is tested through validation of teaching modules by material experts and learning method experts, as well as validation of LKPD by material experts. Based on the validation results, the teaching module obtained a score of 80%, which indicates the